PENGEMBANGAN BAHAN AJAR TERINTEGRASI KEARIFAN LOKAL KABUPATEN SAMBAS MATERI CERITA DARI KAMPUNG HALAMAN MATA PELAJARAN IPAS KELAS III SEKOLAH DASAR - Safa Atika Suri; Agung Hartoyo; Andang Firmansyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to develop supplementary teaching materials integrated with the local wisdom of Sambas Regency for the Stories from Hometown topic in the Natural and Social Sciences (IPAS) subject for third-grade elementary school students and to determine their feasibility and readability levels. The study employed a Research and Development (R&D) method using the ADDIE model, which included the analysis, design, and development stages. A mixed-methods approach was applied, with data collected through interviews and questionnaires. The research subjects consisted of material experts, language experts, media experts, a third-grade teacher, and 28 third-grade students of SD Negeri 43 Dungun Perapakan. The results indicated that the developed teaching materials achieved a very high level of feasibility. Expert evaluations of the material, language, and media aspects each received Category A, classified as “Excellent.” The readability test results also showed very positive responses, with percentages of 100% from the teacher and 89% from the students. Therefore, the supplementary teaching materials integrated with the local wisdom of Sambas Regency were deemed feasible and easy to understand for supporting IPAS learning in elementary schools.